Applying GTM to Enhance Student’s Vocabulary using Crossword Puzzle Game Mobile Application (Word Link) - Suryali, Angie S.; Katemba, Caroline V. (8ISC Proceedings: Arts and Education, 2022)
Vocabulary is one aspect of the English language. The reason why students should have enough vocabulary as a basic requirement to master those four English skills; listening, speaking, reading, and writing. Vocabulary teaching has been incorporated into many of the teaching techniques developed to teach the English language, and it serves the same purposes as those methods. The Grammar Translation Method (GTM) is one of the methods that can be used by teachers in Indonesia. In addition, the researcher used the Word Link application as an example of a crossword puzzle game mobile application. The purpose of this research is to determine whether the Grammar Translation Method (GTM) using the Word Link application will enhance students’ vocabulary. The pre-experimental group consisted of 25 students from Karya Utama elementary school grade 5. A pre-test was conducted at the beginning of the program, followed by a post-test at the end of the 32 hours meeting program. Meetings are held twice per week. Based on the research results, it showed that applying GTM using the Word Link application has a significant positive effect in improving students’ vocabulary. It means that the Crossword puzzle provides a significant contribution in improving the students’ vocabulary, and it is also suggested for teachers to use this method in the English teaching and learning process, especially for elementary school. Keyword : Vocabulary, Grammar Translation Method, Crossword Puzzle Game